2010
DOI: 10.4314/njsr.v8i1.54851
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the severity of intraabdominal Infections; the value of APACHE II Scoring System

Abstract: Intra -abdominal infection continues to defy advances in surgical care with considerable mortality. It is characterized by a spectrum of presentations of varying disease severity. The need to ensure standards for comparing studies and antibiotic trials on intraabdominal infection led to the emergence of several scoring systems. There is paucity of information on this subject in local literature, even though a Nigerian scientist pioneered one of the earliest stratification systems. This is a review of literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(32 reference statements)
2
6
0
Order By: Relevance
“…Another study published by Gonullu et al in 2009 utilizing the Bogota bag technique, however, showed higher (76.4%) failure rates than our study, which may be explained by the inclusion of patients with higher risk score of APACHE II >20 in this study. 7 The incidence of bowel fistula formation in group B patients (13.33%) in our study, was similar to that found in another study published by Orozco et al (13%) utilizing the Bogota's bag and polypropylene mesh for open abdomen management. 16 This incidence of enterocutaneous fistula in our study was lower than that found in the study done by Anderson et al (31%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Another study published by Gonullu et al in 2009 utilizing the Bogota bag technique, however, showed higher (76.4%) failure rates than our study, which may be explained by the inclusion of patients with higher risk score of APACHE II >20 in this study. 7 The incidence of bowel fistula formation in group B patients (13.33%) in our study, was similar to that found in another study published by Orozco et al (13%) utilizing the Bogota's bag and polypropylene mesh for open abdomen management. 16 This incidence of enterocutaneous fistula in our study was lower than that found in the study done by Anderson et al (31%).…”
Section: Discussionsupporting
confidence: 91%
“…6 Patients with scores in this range for both APACHE II and Mannheim Peritonitis Index carried high morbidity and low mortality and hence were included in this study. 7,8 In group A, most of the patients commonly presented with small bowel perforations (43.33% enteric and 3.33% tubercular) followed by pre-pyloric perforations (33.33%), ruptured liver abscess (6.67%) and appendicular perforations (3.33%). In group B, the most common etiology of peritonitis was small bowel perforations (46.67% enteric) followed by pre-pyloric perforations (20%) and ruptured liver abscess (10%).…”
Section: Discussionmentioning
confidence: 99%
“…Various scoring systems have been used to assess the prognosis and outcome of patients with peritonitis. Those used include the Acute Physiological and Chronic Health Evaluation score (APACHE II) (1985), the Mannheim Peritonitis Index (MPI) (1983), the Peritonitis Index Altona (PIA), The Sepsis Severity Score (1983), and the Physiological and Operative Severity Score for Enumeration of Mortality and Morbidity (POSSUM) [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Those used include the Acute Physiological and Chronic Health Evaluation score (APACHE II) (1985), the Mannheim Peritonitis Index (MPI) (1983), the Peritonitis Index Altona (PIA), The Sepsis Severity Score (1983), and the Physiological and Operative Severity Score for Enumeration of Mortality and Morbidity (POSSUM). [3][4][5][6] Mannheim peritonitis index MPI as a prognostic index helps in analysis of prognosis in peritonitis in hollow viscus perforation. The factors that are considered in MPI index are routinely used in assessment of surgical patients, they are easily available, routinely performed, and helps in arrival at a prognosis in fast and effective way.…”
Section: Introductionmentioning
confidence: 99%